1999
DOI: 10.4269/ajtmh.1999.61.869
|View full text |Cite
|
Sign up to set email alerts
|

Safety, immunogenicity, and lot stability of the whole cell/recombinant B subunit (WC/rCTB) cholera vaccine in Peruvian adults and children.

Abstract: Abstract. To assess the safety, immunogenicity, and lot stability of the whole cell/recombinant B subunit cholera vaccine, 2 lots manufactured in June 1991 and February 1992 were tested in January 1995. Two oral doses of vaccine or placebo given 2 weeks apart were given with buffer to 216 Peruvian adults and children. Symptoms were elicited for 3 days after each dose. Serum and plasma specimens obtained from each volunteer before vaccination and 10-14 days after the second dose were tested for vibriocidal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
4
13
1
3
Order By: Relevance
“…Other studies have found immune responses to the killed oral vaccine in developing countries to be weaker [15] but immune responses to live oral vaccine to be stronger, although these responses did not translate into long-term protection [16]. It is noteworthy that vibriocidal antibody levels in the P group in the present study were greater than the antibody levels seen in the previous study in Bangladesh [1], and the response after the first vaccine dose was robust in all groups.…”
Section: Discussioncontrasting
confidence: 57%
“…Other studies have found immune responses to the killed oral vaccine in developing countries to be weaker [15] but immune responses to live oral vaccine to be stronger, although these responses did not translate into long-term protection [16]. It is noteworthy that vibriocidal antibody levels in the P group in the present study were greater than the antibody levels seen in the previous study in Bangladesh [1], and the response after the first vaccine dose was robust in all groups.…”
Section: Discussioncontrasting
confidence: 57%
“…Few direct comparisons have been made of the differences in vibriocidal responses to OCV between younger and older children. In immunogenicity studies of WC-rBS in Peruvian children, younger and older children had comparable seroconversion rates 14 days after the second dose of vaccine (39). In our study, we similarly found no differences in vibriocidal responses between younger and older vaccinated children although a subanalysis disclosed that the youngest children (defined as Յ4 years of age) were less able to mount a vibriocidal response than older children.…”
Section: Discussionsupporting
confidence: 52%
“…In individuals with wild-type V. cholerae infection, we have recently shown that levels of V. cholerae antigen-specific memory B cells are comparable between younger children and older children and adults (22), suggesting that an optimal vaccination strategy could theoretically induce protective immunity in both younger and older children. Despite a number of studies evaluating serological parameters of OCV immunogenicity in children (5,12,39) and one of MBC responses to OCV in adults (2), there are currently no data on memory B cell responses in children receiving oral cholera vaccination. Therefore, the aims of this study were to evaluate acute-phase immune responses in pediatric recipients of an OCV, including characterizing memory B cell responses, and to compare these responses with those seen in children with cholera in Bangladesh.…”
mentioning
confidence: 99%
“…The decline in efficacy for children is similar to the decline in immunity for those immunized parenterally (161). A similar vaccine study of Peruvian children 2-5 years of age, reported that children did not have vibriocidal antibody titers as high as older individuals did (228). Peruvians immunized with two doses of WC (Inaba/Ogawa) plus recombinant CTB vaccines induced a twofold increase in the vibriocidal serum titers; a booster dose after 10 months increased the titers to what was seen initially after the first two doses (11).…”
Section: Anti-v Cholerae Lps Antibodies In Response To Oral Immunizamentioning
confidence: 99%